Examining the Deficiency of Zinc in Febrile Seizures - Attaullah Bizenjo, Saima Rayaz, Mohammad Iqbal, Mohammad Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To examine the deficiency of zinc in febrile seizure cases. Study Design: Prospective study Place and duration of study: Department of Pediatric Medicine Unit 1, Balochistan Institute of Child Health Quetta from 1st January 2022 to 30th June 2022. Methodology: Fifty children suffering from febrile seizures and 50 controls were age and gender matched. The age of the children was between 6 months to 5 years. Each febrile seizure child was clinically diagnosed after the radiological computerized tomography scan imaging as well as electroencephalogram testing and through balanced electrolytes followed by zinc analysis in cases and control. Results: The mean age of the patients with febrile seizures was 35.2±12 months while the controls 35.7±11 months with no significant difference in the age of the both. The majority of the patients were boys (54%) with only 46% girls suffering from febrile seizures. The zinc levels in boys were measured as mean 69.42±20.47 in febrile seizure cases and 92.74±17.63 in controls while in girls they were 71.42±21.02 in febrile seizure cases and 91.73±17.64 in controls respectively. Conclusion: Serum zinc levels found in febrile seizures is lower than the values found in controls with a significant difference suggesting an association of zinc to stimulation and formation of febrile seizures in children. Keywords: Deficiency, Zinc, Febrile seizures